Theme-Based Learning in English Curriculum: Cross-Cultural and Comparative Research on Teachers’ Perspectives in Finland and Hong Kong - Chan, Sze (My University, 2020)
In this study, the actualisation of two similar new pedagogies named phenomenon-based learning (PhBL) and project learning (PjL) in two contexts, Finland and Hong Kong respectively, were investigated. This study aims to explore and understand how the two similar new pedagogies were introduced in the curriculum, and also how the teachers perceive, understand and implement the pedagogies in the classrooms. By comparing: a) the official curricula, b) how teachers perceive and understand the pedagogies, c) the implementation situation, and d) the similarities and differences between the new pedagogies’ actualisation in the two contexts, this study aimed to acquire knowledge about the areas of concern when introducing such new pedagogies, and what could be done to support the practitioners in the process of curriculum reform. For both contexts, the official curricula were analysed. Teachers who were involved in English teaching and learning were interviewed and lessons were observed for supplementary data collection. English teacher trainers professors were also interviewed. The theoretical framework was based on two main foundations: a) a concept on teacher’s cognitive understanding and action, and b) a cross-cultural comparative research approach. Using an adapted thematic-analysis approach, interviews were analysed using NVivo12 software for facilitating rational data comparison. This study demonstrated an overall view on a hybrid method to conduct cross-cultural comparison study and suggested the possible need of identifying key hurdles and key needs when promoting the new pedagogies. Further, this study also provided a number of possible directions for better pedagogy actualisation for future research.
Keywords: Curriculum reform, Finland, Hong Kong, perception, cognitive understanding, implementation, theme-based learning, phenomenon-based learning, project learning, English language teaching and learning, elementary education